Ø§Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© Ø§Ù„ØªØ¹Ø¨ÙŠØ± Ø§Ù„Ù…ØµÙˆØ± ÙˆÙØ¹Ø§Ù„ÙŠØªÙ‡Ø§ ÙÙŠ ØªØ±Ù‚ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ù„Ø·Ù„Ø§Ø¨ Ù…Ø¹Ù‡Ø¯ Ø§Ù„ÙÙ„Ø§Ø ØºÙˆØ±Ù†ØªØ§Ù„Ùˆ - Hairuddin, Hairuddin (Al-Fashahah: Journal of Arabic Education, Linguistics, and Literature, 2021)
This article aims to explain the effectiveness of the pictorial ta'bir method on improving the speaking skills of grade VIII students of Madrasah Tasanawiyah Ma'had al-Falah Limboto Barat. The method used by the author in this article is an experimental method with pre-test and post-test designs. This study shows that (t) Calculate = 8.82 and (t) Table = 1.833, then it is obtained (t) Count> 1.833. The comparison value shows that the alternative hypothesis (Ha) can be accepted, and the null hypothesis (Ho) is rejected. Thus, the implementation of the Ta'bir Mushawwar strategy was effective in improving the speaking skills of grade VIII students of Madrasah Tsanawiyah Ma'had Al Falah Lamboto Barat Gorontalo. And the results of the application of this method have implications for the great public interest in sending their children to Ma'had al-Falah because of the effectiveness of the application of this method, in addition to the popularity of Ma'had is increasingly positive.